Eclipse : living in the shadow of China's economic dominance - Subramanian, Arvind (Peterson Institute for International Economics, 2011)
In his new book, Arvind Subramanian presents the following possibilities: What if, contrary to common belief, China's economic dominance is a present-day reality rather than a faraway possibility? What if the renminbi's takeover of the dollar as the world's reserve currency is not decades, but mere years, away? And what if the United States's economic pre-eminence is not, as many economists and policymakers would like to believe, in its own hands, but China's to determine? Subramanian's analysis is based on a new index of economic dominance grounded in a historical perspective. His examination makes use of real-world examples, comparing China's rise with the past hegemonies of Great Britain and the United States. His attempt to quantify and project economic and currency dominance leads him to the conclusion that China's dominance is not only more imminent, but also broader in scope, and much larger in magnitude, than is currently imagined. He explores the profound effect this might have on the United States, as well as on the global financial and trade system. Subramanian concludes with a series of policy proposals for other nations to reconcile China's rise with continued openness in the global economic order, and to insure against China becoming a malign hegemon.